Analysis of Financial Feasibility and Business Resilience of Small-Scale Capture Fisheries in Grabag District, Purworejo Regency, Central Java - Asnawi Asnawi; Ani Leilani; Shafa Lintang Lauren (PONGGAWA : Journal of Fisheries Socio-Economic, 2026)
This study aims to analyze the financial feasibility and resilience of small-scale capture fisheries under price and production fluctuations in Grabag Sub-district, Purworejo Regency. The analysis focuses on the financial performance of small-scale capture fisheries using feasibility indicators, including Net Present Value (NPV), Internal Rate of Return (IRR), R/C ratio, Break Even Point (BEP), as well as sensitivity and switching value analyses. The study employed a descriptive quantitative approach using primary and secondary data collected through interviews, observations, and document reviews, with a total of 30 respondents. The results indicate that small-scale capture fisheries in Grabag Sub-district are financially highly feasible, as reflected by positive NPV values and IRR levels far exceeding discount rates of 10% and 15%. Sensitivity analysis shows that price and production declines of up to 30% still result in financial feasibility, while switching value analysis demonstrates that the business can withstand substantial reductions in price or production before reaching the non-feasible threshold. These findings suggest that small-scale capture fisheries in Grabag Sub-district have strong financial resilience and promising development prospects.